Implementation of the Sharia Securities Screening List in PT. Aneka Gas Industri TBK - Wibowo, Wildan Rahmat (Islamicate Institute, 2024)
This article examines the implementation of the Sharia Securities Screening List (DES) in PT Aneka Gas Industri Tbk. Using a normative qualitative approach, the study analyzes OJK regulations, DSN-MUI fatwas, and corporate governance practices to assess compliance with Sharia principles. Findings indicate that the company fulfills DES requirements by avoiding prohibited activities and maintaining financial ratios within Sharia thresholds. Governance mechanisms, including board oversight and disclosure practices, support compliance but face challenges in transparency and independent Sharia supervision. The article emphasizes that DES effectiveness depends on harmonized regulation, robust governance, and improved investor literacy. Comparative insights with Malaysia suggest that Indonesia must enhance screening methodologies to strengthen its Islamic capital market. The study contributes theoretically by integrating Islamic finance and governance frameworks and practically by providing recommendations for regulators and corporations to ensure sustainable Sharia compliance in securities markets.